Adipose Tissue SIRT1 Regulates Insulin Sensitizing and Anti-Inflammatory Effects of Berberine - Shan, Yun; Zhang, Shuchen; Gao, Bin; Liang, Shu; Zhang, Hao; Yu, Xizhong; Zhao, Juan; Ye, Lifang; Yang, Qin; Shang, Wenbin (Frontiers in Pharmacology, 2020)
Berberine (BBR), which is an active component of Coptis chinensis Franch, has been reported to improve glucose metabolism and insulin resistance in animal and human studies, predominantly via activation of the 5′-adenosine monophosphate kinase (AMPK) pathway and suppression of the inflammation response. However, the mechanisms underlying the effects of BBR on AMPK and inflammation remain unclear. In this present study, we found that BBR upregulated SIRT1 expression in 3T3L-1 adipocytes and adipose tissue. Inhibition of SIRT1 blunted the BBR-induced increase in glucose consumption and uptake in adipocytes. The BBR-induced activation of the AMPK pathway and AKT phosphorylation in adipocytes and adipose tissue were also attenuated by inhibition or knockout of Sirt1. The BBR-induced improvement of systemic insulin sensitivity was impaired by Sirt1 knockout in HFD-induced obese mice. The suppressing effects of BBR on systemic and local inflammatory responses, such as serum concentrations and expression of inflammatory cytokines, phosphorylation of c-Jun N-terminal kinase (JNK) and IKKβ, and the accumulation of F4/80-positive macrophages in adipose tissue were also attenuated in Sirt1 knockout mice. The BBR-induced decrease in PGC-1α acetylation was reversed by inhibition or knockout of Sirt1 in adipocytes and adipose tissue. Together, these results indicate that adipose tissue SIRT1 is a key regulator of the insulin sensitizing and anti-inflammatory effects of BBR, which contribute to the improvement of metabolic dysregulation.